Dinamika Pemikiran Hukum Islam Kontemporer dalam Menghadapi Arus Modernitas - Novi Arliati; Raisya Aurora A; Adelia Nurinsani; Kurniati Kurniati (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
Modernity, driven by technological advancements and significant social transformations, introduces new challenges to the relevance of Islamic law. This article aims to explore the evolution of Islamic legal thought, providing a clear distinction between classical and contemporary epistemological foundations. It also addresses the urgency of reforming Islamic law to align with the modern era. The research uses a qualitative approach, including literature review and normative-theological analysis, to better understand the shifts within Islamic legal frameworks. The study highlights that modernity has facilitated the expansion of the istinbāṭ method, strengthened the focus on maqāṣid al-syarī‘ah, and encouraged a more contextual and dynamic interpretation of Islamic texts. The research further emphasizes the critical need for epistemological reform within Islamic law to ensure that it remains relevant, adaptive, and capable of fulfilling the legal, social, and moral needs of contemporary society. Such reform is essential for Islamic law to continue being effective and applicable in today’s rapidly changing world.